Gastric cancer – Clinical aspects - J. Bornschein (Microbiota in Health and Disease)
In the year of the 40th anniversary of the official discovery of H. pylori, the association between the infection and gastric cancer has been further investigated and thoroughly reviewed. Articles on PubMed, published between April 2023 and March 2024 were reviewed and studies with a clear clinical focus were included in this review. Several authors presented an excellent overview of the trends of gastric cancer incidence and mortality over the last four decades. These include details on different subtypes of gastric cancer, the respective impact of H. pylori infection as well as factors that modulate regional differences of gastric cancer epidemiology. In line with the general decline of H. pylori prevalence, there is now also more focus on the features of H. pylori negative gastric cancer. Clinically, there was a shift of attention towards early detection and screening to allow diagnosis at a stage when curative, most often endoscopic, treatment is feasible. Similarly, with the proportion of early gastric cancers increasing, a precise assessment of the individual risk for meta-chronous lesions after endoscopic resection is of high importance to allow appropriate surveillance regimens. This includes studies on the impact of modifiable risk factors as well as the relevance of preneoplastic conditions at the time of treatment. While there are some new data on blood-based biomarkers, the field is somewhat stagnating. New interest has been sparked in the influence of the gastric microbiota on the effect of immunotherapy in the palliative setting, but the results are not yet conclusive.